Haldane limits via Lagrangian embeddings - BYKOV, DMITRI VLADIMIROVICH (Elsevier, 2012)
In the present paper we revisit the so-called Haldane limit, i.e. a particular continuum limit, which leads from a spin chain to a sigma model. We use the coherent state formulation of the path integral to reduce the problem to a semiclassical one, which leads us to the observation that the Haldane limit is closely related to a Lagrangian embedding into the classical phase space of the spin chain. Using this property, we find a spin chain whose limit produces a relativistic sigma model with target space the manifold of complete flags U(3)/U3(1). We discuss possible other future applications of Lagrangian/isotropic embeddings in this context.
PUBLISHED
Keywords: Mathematics; Haldane limit